2014
DOI: 10.5194/bgd-11-14319-2014
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Drought in forest understory ecosystems – a novel rainfall reduction experiment

Abstract: Abstract. Climate change is predicted to severely affect precipitation patterns across central Europe. This may reduce water availability during the plant-growing season and hence affect the performance and vitality of forest ecosystems. We established a novel rainfall reduction experiment on nine sites in Germany to investigate drought effects on soil-forest-understory-ecosystems. A realistic, but extreme annual drought with a return period of 40 years, which corresponds to the 2.5% percentile of the annual p… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…We imposed a month‐long drought in which no water was supplied, and a heat‐pulse (at DD 13) that lasted 8 h with maximum air temperatures of approximately 50 °C. The soil moisture stress we induced exceeded even the strong drought conditions for this part of Germany (Gimbel et al ., ). Soil water potential decreased far below the permanent wilting point, a plant physiological threshold, and below the point at which carbon substrate diffusion halts in soils, a microbial environmental limitation (Manzoni et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…We imposed a month‐long drought in which no water was supplied, and a heat‐pulse (at DD 13) that lasted 8 h with maximum air temperatures of approximately 50 °C. The soil moisture stress we induced exceeded even the strong drought conditions for this part of Germany (Gimbel et al ., ). Soil water potential decreased far below the permanent wilting point, a plant physiological threshold, and below the point at which carbon substrate diffusion halts in soils, a microbial environmental limitation (Manzoni et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Numerous studies have explored the C consequences of water stress by investigating extended periods of low precipitation [e.g., Ciais et al ., ; Schwalm et al ., ] or by reducing precipitation experimentally [e.g., Hanson et al ., ; Beier et al ., ; Gimbel et al ., ]. While these studies have greatly improved our understanding of ecosystem sensitivities to water availability [ Bréda et al ., ; van der Molen et al ., ; Vicca et al ., ], their focus on soil water content (SWC) represents a single dimension of how forests experience water stress.…”
Section: Introductionmentioning
confidence: 99%
“…One aspect of global climate change is changing patterns of precipitation (Easterling et al, 2000;Davidson et al, 2004;Gimbel et al, 2015), drought events will be more common and exert a greater impact on most of terrestrial ecosystems functioning (Hasibeder et al, 2015). Global warming induced by increased levels of atmospheric greenhouse gases has elevated the global mean temperature by 0.76 ℃ since 1850 and is expected to continue to increase by another 1.0-3.7 ℃ by the end of this century (IPCC, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Environmental factors such as soil temperature and moisture, strongly relevant to climate change, can influence fine root biomass (Gimbel et al, 2015). For example, it was found that elevated temperature increases root length growth and mortality (Gill and Jackson, 2000), but decreases total root biomass of tree seedlings (Wan et al, 2004).…”
Section: Introductionmentioning
confidence: 99%